6x-8x+10=87-21+10x

Simple and best practice solution for 6x-8x+10=87-21+10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-8x+10=87-21+10x equation:


Simplifying
6x + -8x + 10 = 87 + -21 + 10x

Reorder the terms:
10 + 6x + -8x = 87 + -21 + 10x

Combine like terms: 6x + -8x = -2x
10 + -2x = 87 + -21 + 10x

Combine like terms: 87 + -21 = 66
10 + -2x = 66 + 10x

Solving
10 + -2x = 66 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
10 + -2x + -10x = 66 + 10x + -10x

Combine like terms: -2x + -10x = -12x
10 + -12x = 66 + 10x + -10x

Combine like terms: 10x + -10x = 0
10 + -12x = 66 + 0
10 + -12x = 66

Add '-10' to each side of the equation.
10 + -10 + -12x = 66 + -10

Combine like terms: 10 + -10 = 0
0 + -12x = 66 + -10
-12x = 66 + -10

Combine like terms: 66 + -10 = 56
-12x = 56

Divide each side by '-12'.
x = -4.666666667

Simplifying
x = -4.666666667

See similar equations:

| x-(-11)=18 | | -7(2t+3)=-35 | | s*4-46=-2 | | 49x+1.5=25x+3 | | 3x-7-4x+11=6x-3 | | 12a+12a+7a+7a= | | 40c+8=48c-20 | | -30=-5+5 | | 3x-7-4x+11=6x-7 | | 2f=10 | | 10+5(a-3)=9-2a | | tg(2x)=0.6 | | 2z^2-15z+7=0 | | 7(x-6)=56 | | x^2-10x+6=1 | | 7(3s+4)=133 | | 3z+3z+4z+3+4z+3=132 | | 3f=9 | | 8(2l+8)=112 | | 3x+1+1x+11=180 | | 5*(5*(5*(5+4)+3)+2)+1= | | x+13=111 | | 6k+k-3k+3=19 | | 7h+18=214 | | -2(x+7)=14 | | 2A+2b=bc | | f(2n+1)=f(n)+f(n-1) | | 6x-6=-15 | | (q-9)*4=8 | | (9c+5)(7c-1)=0 | | -10m-11m+13m=16 | | p(x)=2x^3+x^2-49x+8 |

Equations solver categories